Perancangan Aplikasi Pembelajaran Ilmu Fara’idh Berbasis Multimedia - Ira Puspita Sari (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Ilmu Fara’idh is studying the rules of granting inheritance rights to entitled heirs. The law of inheritance has been clearly regulated by Allah SWT in the Qur'an and clarified by the Hadith of the Prophet Muhammad. Especially for Muslims, it is very important to learn Farruid knowledge, because the distribution of inheritance is actually not willing. The improper distribution of inherited knowledge can lead to long-term quarrels and the breakdown of the brotherhood. Fara’idh Science has several materials that contain mathematical value in calculating the division of inheritance. In addition to a lot of material about rules, these rules are very complicated, so that not a few students or even teachers have difficulty understanding the material. The Mutimedia learning system provides a relaxed, relaxed, active and interesting way of learning, because it not only provides material in a monotonous form, but also the traditional learning system will make students easily bored and tend to dislike the material causing inadequate understanding. Therefore, incorporating multimedia systems into learning can attract more user interest and make it easier to understand.